2008
DOI: 10.1021/jp710583n
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Hydration of Model Silica Materials by Exploring Their Multiple Minima Hypersurfaces. The Role of Entropy of Association

Abstract: The influence of molecular water on the structure and formation of silica clusters is modeled with the use of the MMH (multiple minima hypersurfaces) approach. It combines quantum chemical Hamiltonians for the calculation of the internal energy with statistical modeling and formulas for the calculation of thermodynamic functions of association. The structures of the most probable clusters of hydration and some properties of the association with water are proposed. Different simple structures are calculated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…A favorable thermodynamic association implies that the supermolecule will be more stable than the isolated molecules; namely, a greater absolute value of DE assoc corresponds to more energetically favorable associations. The MMH methodology usually works with semiempirical methods [39][40][41][42][43][44] for the evaluation of the energies while using statistical mechanics to obtain thermodynamic properties related to the molecular association. 38 The main procedure of this approach constructs several random non-redundant molecular geometries, starting from the independently optimized structures of the interacting molecules, in order to explore the conguration space of the formed complexes.…”
Section: Multiple Minima Hypersurface Calculationsmentioning
confidence: 99%
“…A favorable thermodynamic association implies that the supermolecule will be more stable than the isolated molecules; namely, a greater absolute value of DE assoc corresponds to more energetically favorable associations. The MMH methodology usually works with semiempirical methods [39][40][41][42][43][44] for the evaluation of the energies while using statistical mechanics to obtain thermodynamic properties related to the molecular association. 38 The main procedure of this approach constructs several random non-redundant molecular geometries, starting from the independently optimized structures of the interacting molecules, in order to explore the conguration space of the formed complexes.…”
Section: Multiple Minima Hypersurface Calculationsmentioning
confidence: 99%
“…In several instances during the DFT computations in this investigation the initially trialled cluster configurations needed to be revised and re-optimised (as outlined in the Computational Details section) in order to find lower-energy states rather than being trapped in a local (but not global) minimum on the potential energy surface. This is a similar (but simpler) approach when compared to the study carried out by Mora-Fonz et al, 4 where low-cost molecular dynamics was used to search configurational space, and the study by Montero-Cabrera et al, 36 where a new approach for searching configurational space using DFT and thermodynamics of association of water was employed. Small clusters as studied in this investigation tend to have only a few possible configurations, and therefore the global minimum should ideally be quite straightforward to find.…”
Section: Implications and Limitations Of This Workmentioning
confidence: 99%
“…Monomer reactivity was estimated by conceptual DFT through global reactivity descriptors and local (condensed) Fukui functions. Reported studies have indicated good correlation between these functions and experimental electrophilic substitution patterns for a range of aromatic heterocyclic compounds, including pyrrole derivatives and silicon-based materials. , Multiple minima hypersurface (MMH) methodology, the validity of which for the study of molecular associations and for conformational analysis has been widely demonstrated by some of the coauthors, was employed for random generation and optimization at semiempirical level of theory of α–α′Py n SiOH ( n = 2, 3). Most stable structures were DFT-refined for conformational analysis.…”
Section: Introductionmentioning
confidence: 99%